Systematic Literature Review: Analysis of Project-based Learning Models from Elementary to High School - Rahman, Ikhwan; Kaema, Muhammad Tolal; Nurhapipah, Nurhapipah; Nelwati, Sasmi; Sabri, Ahmad; Rahmanda, Rega (Al-Ashri: Ilmu-Ilmu Keislaman, 2024)
The project-based learning model is a popular learning model applied at various levels of education in Indonesia. This article examines the characteristics and benefits of implementing the project-based learning model, which has been applied to Indonesian education from primary to senior secondary education. This research was conducted using the “Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method. Article searches were carried out on the Scopus and Google Scholar databases in the publication period 2019-2024. 35 articles focused on discussing the characteristics and benefits of implementing the project learning model in primary to senior secondary education. All articles were analyzed using VOSviewer software with keywords related to project-based learning, elementary school, middle school, and high school. The results of this research found that the application of project-based learning has consistent definitions and characteristics from elementary to high school in Indonesia, but its benefits and application show variations according to the level of cognitive development and learning needs of students. The researcher will discuss all research results in detail and comprehensively in the results and discussion section. These findings can be the first reference for future researchers who want to research in depth the implications of project-based learning at the elementary to high school education levels in Indonesia. Teachers are expected to be able to provide time and design project-based learning that is appropriate to the educational level and abilities of students.